Development and Empirical Testing of a Novel Team Leadership Assessment Measure: A Pilot Study Using Simulated and Live Patient Encounters. Issue 2 (19th February 2019) - Rosenman, Elizabeth D.; Bullard, Mark J.; Jones, Kerin A.; Welsh, Laura; Brolliar, Sarah M.; Levine, Benjamin R.; Grand, James A.; Fernandez, Rosemarie
Abstract: Background: Team leadership is critical to health care resuscitation team performance. There has been increased focus on competency in team leadership behaviors; however, there is still variability in how team leadership is assessed within emergency medicine. The objective of this study was to develop and pilot a novel team leadership assessment measure for emergency medicine resuscitation teams. Methods: Team leadership dimensions and associated behaviors were identified through a systematic literature review and expert consensus. Included behaviors were used to create behaviorally anchored rating scales, which were then revised based on subject matter expert ratings. Four raters from three different academic institutions observed 30 video‐recorded resuscitations (20 simulated and 10 actual patient care resuscitations). Mean leadership scores were calculated. Intraclass coefficients (ICCs) were calculated for each item and for overall leadership scores. Leader scores for the simulation‐based scenarios were compared to external variables including level of training, team process, clinical performance, and team situational awareness. The study was conducted from July 2017 through June 2018. Results: Leadership scores ranged from 2.23 to 4.30 (mean [±SD] = 3.18 [±0.50]). The ICC for the overall score was 0.79 for all observations, 0.87 for simulation‐based observations, and 0.24 for the patient care observations. Team leadership scores on simulation‐based observations did not correlate with available external variables. Conclusions: We developed a novel team leadership assessment measure for emergency medicine resuscitation teams with supporting validity evidence, including content validity and response process. The measure demonstrated acceptable inter‐rater reliability when applied to simulation‐based medical resuscitations; however, this did not translate to trauma resuscitations in the actual patient care setting.